Beyond myopia in communications and the sociology of media. Issue 5 (4th April 2023) - Kidd, Dustin; Recuber, Timothy; Atwell, Matt; Burgese, Tyler; Chelius, Andrew; DeMarco, Jaggar; Gallant, Dana; Guidry, Benjamin; Hartenbaum, Glen; Joyce, Caitlin; Ki, Ye Ju; McDonald, Kyle; et al.
ABSTRACT: This special issue of Information, Communication, and Society (ICS) is edited by the Communication, Information Technologies, and Media Sociology (CITAMS) section of the American Sociological Association and includes papers that were first presented at either the 2021 or 2022 ASA meetings or Media Sociology Symposia. For this special issue, an innovative editorial approach was taken that brought the editing process into a graduate classroom. That process is described below along with a brief introduction to themes of the selected articles. Key themes for this special issue include content analysis, ethics, privacy, new economy, and digital inequality.